Postnatal growth of forelimb musculo-tendinous systems in sigmodontine rats (Rodentia: Cricetidae) - Carrizo, Luz Valeria (2018)
The musculo-tendinous system is responsible for generating and transmitting forces necessary to produce and control body movements. The focus of this study was to investigate ontogenetic patterns in the growth of forelimb muscles and tendons in 4 sigmodontine rodents (ambulatory Akodon, quadrupedal saltatorial Eligmodontia, scansorial Oligoryzomys, and semifossorial Oxymycterus) and to discover if these patterns differ with respect to species-locomotor mode. We examined forelimbs of 64 specimens including juveniles, young adults, and adults, and removed and measured 12 muscles and 7 tendons. The evolution of morphology is reflected in both static and ontogenetic allometric patterns. The general allometric pattern revealed by our data is one of decreased growth rate with larger size, because all morphological variables exhibit negative allometry. Patterns of allometry in the musculo-tendinous system may represent adaptations to specific habitat requirements. These patterns differed among species, and hence among locomotor types: 7 morphological variables showed subtle differences between species-locomotor types, while the trends within 3 species-locomotor types did not differ. The strongest patterns were associated to the muscles and tendons related to extension of the arm and flexion of the wrist.